Implementasi Pembelajaran Buku Pengasuhan Berbasis Muslim Peduli Lingkungan untuk Membentuk Karakter Siswa - Junedi Junedi; Wahidin Wahidin (Fakultas Agama Islam Universitas Billfath, 2022)
The purpose of this study was to determine the concept of learning Islamic parenting books about caring for the environment, carrying out learning about Muslim parenting books caring for the environment, and shaping the personality of students by learning Muslim parenting books. Madrasah Tsanawiyah Al Irsyad Tengaran, Semarang, Academic Year 2020/2021. This research is a qualitative research and case study method. The subjects in this study were the head of foster care, dormitory caregivers, Musyrif, and Madrasah students. The technique used is data collection through observation, interviews, and documentation. The results of the research that have been carried out concluded that by integrating Muslim-based childcare activities in the environment, the concept of Muslim-based childcare environment has been included in the parenting curriculum. And through various slogans to socialize the importance of keeping the surrounding environment clean. At MTs Al Irsyad Tengaran Semarang Regency, the learning environment for parenting Muslim parenting books has an impact on behavior change, because the change in awareness has been formed through educational interactions in the form of sociology, psychology, and practical significance, which in turn allows children to have cognitive abilities, Emotional abilities and psychological abilities enable children to have natural views, awareness, knowledge, values, attitudes, skills and participation